Regenerative mesenchymal stem cell‐derived extracellular vesicles: A potential alternative to cell‐based therapy in viral infection and disease damage control. Issue 6 (5th September 2022) - Ipinmoroti, Ayodeji O.; Pandit, Rachana; Matthews, Qiana L.
Abstract: Extracellular vesicles (EVs) released by regenerative cells such as mesenchymal stem cells are effective facilitators of healing, therapy, and repair. Conversely, EVs released from infected and/or diseased cells could be useful as markers in the detection and diagnosis of disease conditions such as cancer at their earliest most detectable, and treatable stage. A very important type of EVs, termed exosomes offer a hypothetical new paradigm in disease detection, diagnosis, and treatment. A broad range of exosome‐based biomedical and therapeutic applications are now being evaluated in recent clinical trials. Exosomes are found in virtually all bodily fluids and cells and are capable of crossing tight junctions and toughly regulated boundaries such as the blood–brain barrier. Exosomes' expedition ends when they are taken up by bystander cells which corroborates the fact that they are conduits for cells releasing them. Exosomes released by diseased cells have been associated with cell‐to‐cell progression of diseases like viral disease, neurodegeneration, and certain cancers. Due to high discrimination in most disease conditions, exosome uptake is usually cell‐specific. Lots of research evidence have revealed that infusion of exosomes derived from regenerative cells such as stem cells could impede the development of certain infections and age‐related diseases by activating self‐repair machinery through RNA, DNA, protein, and lipid transfer between cells in patients. They have also been demonstrated in the restoration of the circulating population of exosomes in tissues and the fluid of recipients. The first human clinical trials of exosome therapies are now underway, establishing the future of regenerative exosome in regenerative medicine. This article is categorized under: Cancer > Stem Cells and Development Immune System Diseases > Stem Cells and Development Immune System Diseases > Molecular and Cellular Physiology Abstract : Regenerative mesenchymal stem cell‐derived extracellular vesicles (MSC‐EVs): a potential alternative to cell‐based therapy in viral infection and disease damage control. MSC‐EVs may directly stimulating target cells for repair immune cell activation and anti‐inflammatory regulation. MSC‐EVs may also modulate tissue and organ repair and formation of new blood vessel in degenerative disease and disease induced injury.